2013
DOI: 10.1038/srep01686
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of novel β coronavirus replication by a combination of interferon-α2b and ribavirin

Abstract: The identification of a novel β coronavirus, nCoV, as the causative agent of severe respiratory illness in humans originating in Saudi Arabia, Qatar and Jordan has raised concerns about the possibility of a coronavirus pandemic similar to that of SARS-CoV. As a definitive treatment regimen has never been thoroughly evaluated for coronavirus infections, there is an urgent need to rapidly identify potential therapeutics to address future cases of nCoV. To determine an intervention strategy, the effect of interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
306
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(314 citation statements)
references
References 46 publications
3
306
0
5
Order By: Relevance
“…In vitro, ribavirin showed a reduction in MERS-CoV replication, but the concentrations required to achieve beneficial effects were higher than what is achievable in humans. Therefore, the risk is likely to exceed the possible benefit when ribavirin is used as a monotherapy (51). In addition, rhesus macaque models showed that a combination of INF-α2b and ribavirin improved clinical outcomes and reduced the severity of the illness.…”
Section: Managementmentioning
confidence: 99%
“…In vitro, ribavirin showed a reduction in MERS-CoV replication, but the concentrations required to achieve beneficial effects were higher than what is achievable in humans. Therefore, the risk is likely to exceed the possible benefit when ribavirin is used as a monotherapy (51). In addition, rhesus macaque models showed that a combination of INF-α2b and ribavirin improved clinical outcomes and reduced the severity of the illness.…”
Section: Managementmentioning
confidence: 99%
“…In vitro studies showed that ribavirin and interferon exhibit anti-MERS-CoV activity [11]. In vitro activity of interferon was further enhanced by the addition of ribavirin [30]. Recently, animal studies utilizing Rhesus Macaque monkeys infected with MERS-CoV were published [31][32][33].…”
mentioning
confidence: 99%
“…It is possible the reason for this reactivation is the fading of the effect of the last dose of PEG-INF α2b which was administered ten days before, resulting in the patient receiving ribavirin monotherapy for three days. Even though this reactivation seemed to be of little clinical significance, it may indicate that monotherapy with lower doses of ribavirin is not sufficient to inhibit the replication of MERS-CoV, therefore, supporting the proposed synergistic effect of PEG-IFN α and ribavirin [4].…”
Section: Discussionmentioning
confidence: 96%
“…This was based mainly on the potential harmful side effects of the combination. In addition, the use of ribavirin alone for the management of MERS-CoV infection was also believed to be associated with an unfavorable safety profile since high doses of the drug were assumed to be needed to approach the required inhibitory concentration in vivo [4].…”
Section: Discussionmentioning
confidence: 99%